Keterlibatan Gereja Katolik Mendukung Moderasi Beragama Berorientasi Pada Komitmen Kebangsaan - Afrianus Darung; Yohanes Yuda (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2021)
This study aims to determine the involvement of the Catholic Church in supporting religious moderation oriented towards national commitment in Indonesia. This study uses a literature research approach by reviewing books, literature, notes, and various reports related to religious moderation. Through this research, it can be concluded that: first, the involvement of the Catholic Church in supporting religious moderation oriented towards national commitment is contained in the statement of the magisterium of the Catholic Church. Second, statements reflecting religious moderation are found in the Church's Magisterium documents, namely: Gaudium et Spes, Pacem in Terris, Dignitatis Humanae, Nostra Aetate, KWI Pastoral Notes, and Pastor's Letters. Third, religious moderation by the Catholic Church has produced moderate figures with the spirit of nationalism in realizing Indonesia's national commitment. Fourth, the concrete involvement of the teachings of the Catholic Church is reflected in the attitude and real action of caring in providing assistance to the community regardless of differences and respect for religious people who celebrate religious holidays through friendship visits.